La competencia de investigación en el grado de trabajo social en las universidades de Andalucía (España) - Morcillo Martínez, Juana María; Ochando Ramírez, María Victoria (Interdisciplinaria. Revista de Psicología y Ciencias Afines, 2025)
Esta investigación tiene como objetivo identificar en qué medida la competencia específica de investigación está presente en las asignaturas de tipología: básica, obligatoria y optativa de los planes de estudio de las enseñanzas conducentes a la obtención del título universitario de grado de trabajo social en las universidades públicas de Andalucía. Para ello, se ha realizado una revisión documental, teniendo como fuente las guías docentes, publicadas en las páginas webs, del curso 2021/2022, de las universidades públicas analizadas. Asimismo, se han cotejado las memorias con el plan de estudios donde se establece que el título de grado en trabajo social consta de 240 créditos distribuidos en cuatro cursos académicos. Del mismo modo, se han establecido categorías para cada universidad estudiada, donde se han incluido: asignaturas, cursos, cuatrimestre, tipología de asignaturas, cada una con la relación de competencias descritas en su correspondiente guía docente. Esto ha permitido identificar un total de 110 asignaturas que tenían incluida la competencia específica de investigación. Se evidencia que la competencia de investigación se encuentra presente en asignaturas básicas, obligatorias y optativas de todos los cursos en las universidades estudiadas. Sin embargo, no tiene la misma presencia en la composición del título que otras competencias orientadas a la intervención social. Es por ello que se considera esencial la formación en competencias, entre ellas la de investigación, ya que de la misma dependerá el desarrollo de la praxis profesional y la calidad de los servicios prestados.
Research competence in the degree of social work in the universities of Andalusia (Spain)
The training given in the degree of social work in the public universities of Andalusia is nourished by knowledge with a theoretical and practical approach that trains students for the practice of the profession. Research, therefore, is integrated within the competencies of the profession. In any case, although there are many contributions that highlight the value of research competence for social work, the truth is that research is still a pending subject for the profession, with a focus exclusively linked to academic contexts (Carbonero, Raya et al., 2020). The objective of this research is to identify the extent to which the specific competence of research is present in the basic, compulsory and optional subjects of the curricula of the courses leading to the university degree in social work in the public universities of Andalusia. For this purpose, a documentary review of the degree reports and the teaching guides for the 2021-2022 academic year published on the institutional web pages of the Faculties of Social Work has been carried out. A qualitative ethodology was used, with a descriptive design, through the documentary review technique. Once the information was collected, it was tabulated using an Excel workbook. In the same, categories have been established: subjects, courses, four-month period, typology of subjects, each one with the relation of competences described in its corresponding teaching guide. Next, the information was processed according to the and a content analysis was carried out. This made it possible to identify a total of 110 subjects that included the specific research competency. Finally, the results were triangulated with the bibliographic review. The results obtained show that, although a variety of basic, compulsory and optional subjects have been found in the four courses that make up the social work degree study plans of the Andalusian public universities, it should be noted that the presence of the specific competence of research in the social work degrees of the universities of Almería, Cádiz, Granada, Jaén, Huelva, Málaga and Pablo de Olavide in Seville is limited. The Andalusian universities have established their own configuration of subjects, distinguishing between those with a content more focused on research, and others that integrate the research competence from a focus more linked to Social Work. There are also subjects that integrate research from the different disciplines of the Social Sciences. In general, it has been seen that the specific competence of research does not have the same presence in the composition of the degree as other competences oriented to social intervention. For this reason, it is considered essential to continue reflecting on the training in competencies given to future social workers, since their professional practice and the quality of the services provided in social welfare institutions will depend to a large extent on it. In short, this research has made it possible to respond to the objective set, identifying the presence of the specific competence of research in the universities studied that teach the degree in social work. A proactive process must be promoted in the configuration of the degree in social work in the public universities of the Autonomous Community of Andalusia, which must continue to offer the achievement of the objective of providing social workers with the necessary training that demands and requires the acquisition of competencies, including research. Social work research is necessary, not only to generate a body of knowledge based on the systematization of practice (Verde, 2011), but also as an instrument that makes it possible to identify new emerging challenges. Hence the training in the specific competence of research in the degree of social work should continue to strive.
Keywords: trabajo social; universidades de Andalucía; competencia específica; investigación; asignaturas; social work; Andalusian universities; specific competence; research; subjects